15th International Conference on Concentrator Photovoltaic Systems (CPV-15) 2019
DOI: 10.1063/1.5123901
|View full text |Cite
|
Sign up to set email alerts
|

New insights into the thermally activated defects in n-type float-zone silicon

Abstract: Float-zone silicon has been long assumed to be bulk defect free and stable. Nevertheless, recently it was found that upon annealing between 450 °C to 700 °C detrimental defects can be activated in this material. Previous studies via deep level transient spectroscopy have identified several defect levels. However, it is still not clear which of these levels have a substantial impact on the minority carrier lifetime. In this study, we determine the recombination parameters of the dominant defect level using a co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 19 publications
0
16
0
Order By: Relevance
“…Rougieux et al demonstrated that the detrimental, lifetime‐reducing impact of the bulk defects can be mitigated to some extent when wafers are thermally processed with hydrogen‐containing capping layers such as atomic layer deposition (ALD)–Al 2 O 3 or (preferably) plasma enhanced chemical vapor deposition (PECVD)–SiN x :H. [ 6 ] Very recently, it was shown that the bulk lifetime of a degraded sample can be improved by one order of magnitude by an annealing of the wafer with a PECVD–SiN x :H layer. [ 9 ]…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Rougieux et al demonstrated that the detrimental, lifetime‐reducing impact of the bulk defects can be mitigated to some extent when wafers are thermally processed with hydrogen‐containing capping layers such as atomic layer deposition (ALD)–Al 2 O 3 or (preferably) plasma enhanced chemical vapor deposition (PECVD)–SiN x :H. [ 6 ] Very recently, it was shown that the bulk lifetime of a degraded sample can be improved by one order of magnitude by an annealing of the wafer with a PECVD–SiN x :H layer. [ 9 ]…”
Section: Resultsmentioning
confidence: 99%
“…[ 6–8 ] Hydrogen (from H‐rich dielectric coatings) was proposed to mitigate the effects of bulk lifetime degradation. [ 6,9 ] We will demonstrate that the passivating effect of H is not permanent.…”
Section: Introductionmentioning
confidence: 93%
“…Activation anneals for aluminum oxide surface passivation are also often performed in this temperature range [20]. Previous studies found that these thermally activated defects can be partially passivated via hydrogenation [19], [21], [22]. Therefore, these defects could be activated during the surface passivation process, but also be partially passivated by the hydrogen introduced during the dielectric deposition process.…”
Section: Introductionmentioning
confidence: 99%
“…It is therefore primordial to identify and characterize bulk defects in order to eliminate or at least reduce their impact. Techniques such as temperature-and injectiondependent lifetimes spectroscopy (TIDLS) 5 enables characterization of a wide range of Si bulk defects, such as copper 6 , aluminium 7,8 , chromium 9,10 , iron 11,12 and many more [13][14][15][16][17] . To identify defects, the Shockley-Read-Hall (SRH) equation 18,19 that describes the impact of a defect on the overall minority carrier lifetime is often used to fit the lifetime measurements 20 .…”
Section: Introductionmentioning
confidence: 99%
“…By repeating the process for each temperature-dependent measurement, different DPSS curves are determined. These curves usually intersect at two points that indicate the possible combinations of the defect parameters, with one set of parameters in the upper bandgap and one in the lower bandgap [7][8][9][10][11][12][13]21 . This method, henceforth referred to as the 'traditional approach', has been refined over the years, such as linearizing the SRH equation under specific conditions 14,22 or applying faster convergence techniques to find the intersection points 21 .…”
Section: Introductionmentioning
confidence: 99%